Structure of extremely nanosized and confined In-O species in ordered porous materials - Ramallo López, José Martín (2003)
Perturbed-angular correlation, x-ray absorption, and small-angle x-ray scattering spectroscopies were suitably combined to elucidate the local structure of highly diluted and dispersed InOₓ species confined in the porousof the ZSM5 zeolite. This novel approach allow us to determined the structure of extremely nanosized In-O species exchanged inside the 10-atom-ring channel of the zeolite, and to quantify the amount of In₂O₃ crystallites deposited onto the external zeolite surface.